TOOL EDUCATION MODEL OF INFORMATION TECHNOLOGY CULTURE FOR PROSPECTIVE TECHNICIAN IN EDUCATIONAL ENVIRONMENT OF POLYTECHNIC COLLEGE - Vitaly B. Dudka (Advanced Engineering Research)
The tool education model of information technology culture of the prospective expert amidst the cultural-educational environment of the polytechnic college is considered. Its blocks are described.